Instituições bancárias e transmissão de política monetária: um estudo microeconômico aplicado ao Brasil - Felipe Augusto de Araujo (2012)
This work investigates the existence of a bank lending channel of monetary policy transmission in Brazil in the years 2000 to 2011. We use bank-level data obtained from the Brazilian Central Bank. Our results indicate that the loan supply of more capitalized and more prudent banks are more sensitive to monetary policy tightening than the supply of the average bank. There is no evidence that more liquid banks, the ones that are part of a conglomerate and banks with a foreign control respond differently to monetary contractions. These results do not allow us to decisively conclude either in favor or against the existence of such a channel of monetary transmission. They can, however, have important consequences for the conduct of monetary policy in Brazil.